A Workload-Balance Crossover Operation in a Genetic Algorithm solving an Airline Crew Rostering Problem - อ้นสวน, กชพร; อินทิยศ, บุญฤทธิ์; จีนอนันต์, ชวลิต (Frontiers in Engineering Innovation Research, 2012)
The airline crew rostering problem is complex and very difficult to find the answer in a suitable time because the requirements are complicated and the size of the crew and flight are very large. This paper proposes the Genetic Algorithm to find a crew rostering solution for the case study of Thai Airways. The objective is to balance the workload and perdiem for each crew member. A non-binary encoding is used in the chromosome. The mutation and crossover are modified to accommodate the objective of the problem. The algorithm is tested with data from Thai Airways and the efficiency of the algorithm and the analysis of the result are discussed.